Efektifitas Latihan Senam Diabetes Terhadap Penurunan Glukosa Darah - Herni Herni; Syahruddin Syahruddin; Andi Atssam Mappanyukki (Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2022)
Many elderly have diabetes mellitus (DM). Therefore, it is necessary to design a form of exercise in the form of gymnastics to reduce the percentage of diabetes mellitus. This study aims to reduce the prevalence of diabetes mellitus in diabetics. The type of research is quasi-experimental, involving the treatment variable being diabetes mellitus exercise (LSDM) while the response variable is blood glucose level (KGD). The research sample, namely members of the Makassar Rappocini BKMT, 10 women, aged 50-55 years, using a purposive sampling technique. The instruments used are auto-check, lancet, and strip auto-check (a tool used to detect sugar levels). The data analysis technique used is paired t-test analysis. The results showed that LSDM was effective in reducing KGD in diabetics (p <0.05). Conclusion LSDM is effective in reducing KGD for DM patients with a frequency of at least 3 times a week with a duration of 30-60 minutes and a low rhythmic tempo. The research recommendation is for people with DM, it is very appropriate to apply LSDM independently as a non-pharmacological therapy method to reduce KGD